2010
DOI: 10.1175/2009jtecha1327.1
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a Multichannel Water Vapor Raman Lidar through Noncollocated Operational Soundings: Optimization and Characterization of Accuracy and Variability

Abstract: This paper presents a parametric automatic procedure to calibrate the multichannel Rayleigh-Mie-Raman lidar at the Institute for Atmospheric Science and Climate of the Italian National Research Council (ISAC-CNR) in Tor Vergata, Rome, Italy, using as a reference the operational 0000 UTC soundings at the WMO station 16245 (Pratica di Mare) located about 25 km southwest of the lidar site. The procedure, which is applied to both channels of the system, first identifies portions of the lidar and radiosonde profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…These values are consistent to those obtained with other instruments (Whiteman et al, 2007;Hoareau et al, 2009;Dionisi et al, 2010;Leblanc et al, 2012). This variability clearly emerges for the 8 h lidar session between the 15:00 UTC on the 11 April and the 00:00 UTC on 12 April (highlighted by the black vertical dotted lines in the plot) where the calibration factor varies from almost 270 to 150.…”
Section: Total Column Calibrationsupporting
confidence: 89%
See 1 more Smart Citation
“…These values are consistent to those obtained with other instruments (Whiteman et al, 2007;Hoareau et al, 2009;Dionisi et al, 2010;Leblanc et al, 2012). This variability clearly emerges for the 8 h lidar session between the 15:00 UTC on the 11 April and the 00:00 UTC on 12 April (highlighted by the black vertical dotted lines in the plot) where the calibration factor varies from almost 270 to 150.…”
Section: Total Column Calibrationsupporting
confidence: 89%
“…In particular, preliminary results on the accuracy of Raman water vapor measurements in the UTLS have been obtained (Whiteman et al, 2011b(Whiteman et al, , 2012Leblanc et al, 2012), and different calibration methodologies have been developed Leblanc et al, 2011;Hoareau et al, 2009;Dionisi et al, 2010;Reichardt et al, 2012, Bock et al, 2013. The aim is to set up a lidar reference network for upper-air climate observations of water vapor such as GRUAN (GCOS Reference Upper-Air Network, Immler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The vertical smoothing amounts to 270 m. Only an altitude region from 2 up to 5 km is regarded for the regression to exclude boundary layer inhomogeneities in the water vapour structure and to avoid differences due to the RS drift in higher altitudes. Using this method, Dionisi et al (2010) found a variability in the calibration factor of about 10 %.…”
Section: Regression Methodsmentioning
confidence: 96%
“…The influence of different temporal and spatial matching and its impact on the system has been previously discussed in the literature (e.g. Sussmann et al, 2009;Schneider et al, 2010;Vogelmann et al, 2011;Dionisi et al, 2010).…”
Section: Water Vapor Profilesmentioning
confidence: 99%